Internalisasi Nilai-Nilai Karakter Jujur dalam Pembelajaran PAI di SDN 261 Margahayu Raya Kota Bandung - Fauziah Nurul Azizah; Muhammad Ahyad; Muspi Maripatul Hidayat; Sufyan Rangga Kusumah; Vivi Aisyah; Hani Hadiati Pujawardani (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
This research aims to explore the phenomenon of internalizing the values of honesty in Islamic Religious Education learning at SDN 261 Margahayu Raya, Bandung City. By recognizing various forms of dishonesty and teaching the values of honesty from an early age, character education is expected to shape a generation that is honest, responsible, and has integrity. Through a descriptive qualitative approach, the research was conducted using interviews as the method of data collection. The results of the research show that strategies to cultivate honest character are implemented through learning that narrates examples of honesty, and through Islmaic Religious Edcation learning, students are taught to respect differences and uphold the value of harmony among people of different religions. Islmaic Religious Edcation teachers play a crucial role in shaping students' character and morals, so it is expected that students can become individuals who are faithful, pious, virtuous, and able to contribute positively to society in accordance with Islamic values. This research contributes to understanding the importance of internalizing the values of honest character in Islamic education at elementary schools.